Desenvolvimento tecnológico de produtos secos redispersíveis a partir de nanoestruturas contendo tioconazol - Ribeiro, Roseane Fagundes (2013)
Spray-drying and freeze-drying are dehydration techniques which serve as alternative to increase the stability of formulations which are in aqueous medium. Therefore, this study objectived the development of redispersible dried products prepared from suspensions of polymeric nanocapsules and nanoemulsions using tioconazole, an antifungal. The suspension of nanocapsules, prepared using poli(-caprolactona) - PCL and Eudragit® RS100 polymers, and nanoemulsions containing tioconazole (1.0 mg/ml) were evaluated in relation to mean particles size, drug content, pH and encapsulation efficiency, and after preparation, showed physicochemical characteristics suitable: mean particles size in the nanometer range (110 210 nm), polydispersity index below 0.20, drug content near to theoretical and encapsulation efficiency of approximately 100 % and 86 % for the PCL and Eudragit® RS100 nanocapsules, respectively. Furthermore, the formulations have been stable for 30 days. After, the liquid formulations were subjected to spray-drying and/or freeze-drying using lactose and trehalose as adjuvants in a proportion of 10 % (w/v). The dried products were characterized in relation to yield, index resuspension in water, drug content, moisture and morphology. Regardless of the method of dehydration and adjuvant, the dried products presented satisfactory physicochemical characteristics: yield 50 100 % (depending on the technique of dehydration), drug content near to theoretical, percentage of moisture of less than 4.2 %, good redispersion in water, is possible to verify the presence of nanometric and micrometric particles (by laser diffraction), and the recovery of nanometer size similar to the original liquid formulation, after filtration (photon correlation spectroscopy). Morphological analysis showed the presence of rounded particles for the powders obtained by spray-drying and irregular to those obtained by freeze-drying. Dried products were stable for 30 days, however, the powders obtained from nanoemulsions and nanocapsules of Eudragit® RS100, by spray-drying and lactose as adjuvant showed a decrease in tioconazole content. The suspensions of nanocapsules and nanoemulsions and their respective dried products containing tioconazole showed antifungal activity against the yeast C. albicans, demonstrating that the dehydration process did not affect the action of the drug. Evaluation of in vitro release of the drug by the technique of dialysis bags showed that dried products prepared from nanocapsules were able to promote the control release of the drug, especially the dried products obtained from nanocapsules of PCL by spray-drying, which showed more tioconazole control release at time of 48 hours.